Cerebral Fat Macroembolism: Diagnosic Tools with Spectral Imaging - Mathilde Haegeman; Douglas Lacomblez; Antoine Loubet (Journal of the Belgian Society of Radiology)
Teaching point: Spectral tomography offers valuable complementary diagnostic tools in the setting of cerebral fat macroembolism, a rare condition often presenting with nonspecific clinical symptoms.